PEMBIAYAAN UMKM DAN LIKUIDITAS TERHADAP RESIKO PEMBIAYAAN BANK UMUM SYARIAH DI INDONESIA PERIODE 2019-2021 - Herlina; Hairunnisa; Puput Melana Sari (LA RIBA: Jurnal Perbankan Syariah, 2022)
Poor financing quality can affect company profits and revenues, decreased profits have an impact on the ability of banks to channel financing which causes Islamic banking to experience financing risks or problematic financing. This study aims to find out how the independent variables (MSME financing and liquidity) influence the dependent variable (financing risk) of Islamic commercial banks in Indonesia for the 2019-2021 period. The method used in this study is quantitative with descriptive statistics, the classic assumption test, namely the normality test, multicollinearity, autocorrelation, and heteroscedasticity test, is also equipped with hypothesis testing, namely the t (partial) test and f (simultaneous) test. The population used in this study is the statistical financial reports of Islamic commercial banks with samples of MSME, FDR and NPF data for 2019-2021 obtained from the Financial Services Authority. From OJK data, the results show that MSME financing does not have a significant effect on financing risk because there is a guarantee from the government to the community, namely the people's business credit program (KUR) which is channeled through Islamic banking institutions, good and bad bank liquidity does not have an impact on financing risks and financing risks occur because problematic financing from customers is not caused by Islamic banking institutions or liquidity owned by Islamic banking. The conclusion of this study is that the Ho hypothesis is accepted, showing that one or both of the independent variables (MSME financing and liquidity) have no effect on the dependent variable (financing risk) of Islamic general banks in Indonesia for the 2019-2021 period.